A two-component, multimeric endolysin encoded by a single gene - Proença, Daniela (2017)
"Bacteriophage endolysins are bacterial cell wall degrading enzymes whose potential to fight bacterial infections has been intensively studied. Endolysins from Gram-positive systems are typically described as monomeric and as having a modular structure consisting of one or two N-terminal catalytic domains (CDs) linked to a C-terminal region responsible for cell wall binding (CWB). We show here that expression of the endolysin gene lys170 of the enterococcal phage F170/08 results in two products, the expected full length endolysin (Lys170FL) and a C-terminal fragment corresponding to the CWB domain (CWB170). The latter is produced from an in-frame, alternative translation start site. Both polypeptides interact to form the fully active endolysin. Biochemical data strongly support a model where Lys170 is made of one monomer of Lys170FL associated with up to three CWB170 subunits, which are responsible for efficient endolysin binding to its substrate. Bioinformatics analysis indicates that similar secondary translation start signals may be used to produce and add independent CWB170-like subunits to different enzymatic specificities. The particular configuration of endolysin Lys170 uncovers a new mode of increasing the number of CWB motifs associated to CD modules, as an alternative to the tandem repetition typically found in monomeric cell wall hydrolases."